Relationship of Managerial Creativity With Demographic Variables: Understanding the Relationship between Managerial Creativity and Organizational Effectiveness (Journal of Advances and Scholarly Researches in Allied Education, 2011)
The concept of organizational effectiveness is animportant innovation in business management. Initially, organizationaleffectiveness focused on how well an organization compete, how quickly theybring products to the market, their status in the community, theirattractiveness to potential market and their profitability. In other words,organizational effectiveness considers how well an organization performsbusiness. Instead of defining corporate success by a few short-term measures,such as sales or profit, it fostered a holistic long-term perspective. Thisexpanded perspective that resulted from a focus on the overall effectiveness ofan organization has become central to corporate survival and success in today’seconomy. The focus on people, their performance, innovation and creativity isthe professional concern of organizational effectiveness. The current researchattempts to define a broad perspective on organizational effectiveness and itsrelation to managerial creativity.